STRATEGI KELUARGA MISKIN DALAM MEMENUHI KEBUTUHAN HIDUP (Studi Kasus : Terhadap Suaminya yang Tidak Memiliki Pekerjaan Tetap di Kampung Pasar Gompong Nagari Kambang Barat Kecematan Lengayang Pesisir Selatan) - -, Srimadeni - (Pendidikan Sosiologi, 2014)
and it are a cluster people that live in one home. They still have relationship a familly/relationship a marriage, birth, adopted and ect. Familly the are father, mother, and child. Husband having responsibility to complied need for living member of familly all thought primary and not primary. So that, with nothing job of a husband, so, wife and child to in volve her self to work for completed need for living. In this reseach purpose are: 1) identify backround of husband that donât have working. 2) description familly strategy to complied need for living, toward her husband that donât have working. Thoery that used theory of Weber about Social Action and this reseach approach and qualitatif with descriptive, type to develop a problem that reseached. Collecting technique of data through observasion, interview, and document study. Analysis technique of data done as description type that are: 1) Data collecting, 2) Data Reducation, 3) Data offening, 4) consclusion. This reseach location do at Kampung Pasar Gompong Nagari Kambang Barat Sub-Distric lenggayang Pesisir Selatan.Based on the reseach result get conclusion as: Human needs that they must complete to primary needs although non primary, and as for factor that influenced need for living that is: nature environment factor, education factor, job factor, age factor, and physigve factor. Familly strategy to complied needs for living: 1) strategy of husband to complied needs for living of familly. 2) strategy of wife to complied needs for living of familly. 3) strategy of child to help economic matters or familly.